Risk predictors and outcomes of infective endocarditis among adult patients with congenital heart disease. (3rd October 2022) - Fedchenko, M; Giang, K W; Snygg-Martin, U; Dellborg, M; Mandalenakis, Z
Abstract: Background: Infective endocarditis (IE) is a serious disease associated with increased morbidity and mortality. Patients with adult congenital heart disease (ACHD) have been reported to be at a particularly increased risk of infective endocarditis (IE). Purpose: To investigate the risk predictors of IE, and the long-term risk of IE among ACHD patients aged 18–65 years, compared with matched controls without ACHD, in a nationwide setting. Methods: All patients with ACHD in Sweden born in years 1952–1999 and who survived until 18 years of age were followed in the National Patient Register and Cause of Death Register until year 2017. For each case of ACHD, approximately ten controls without ACHD were randomly selected from the Total Population Register and matched by birth year and sex. The study population was followed from 18 years of age and until a first time diagnosis of IE, death or end of study. Both comorbidities and occurrence of ACHD related surgery were collected from 1970 and onwards. Cox proportional hazard models were used to predict the risk of IE. Results: Altogether, 36, 189 ACHD patients and 403, 962 controls without ACHD were included. A total of 706 (1.95%) ACHD patients and 147 (0.04%) controls developed IE during a median follow-up of 15.5 (interquartile range (IQR) 6.9–28.5) years (ACHD) and 15.5 (IQR 7.5–28.5) years (controls). ACHD patients were somewhat younger at age of IE diagnosis compared with controls, median age 33.9 (IQR 25.4–44.1) years in ACHD vs 39.8 (IQR 30.6–52.0) years in controls. The overall risk of IE was markedly higher among ACHD patients compared with controls, with a hazard ratio (HR) of 54.8 (95% confidence interval (CI), 45.9–65.5). More than one third of the ACHD patients with IE (n=272, 38.5%) had undergone any kind of previous congenital heart surgery whereof 122 (44.9%) had undergone valve replacement (mechanical/biological) prior to IE. In ACHD patients, the most important risk predictors for IE were ACHD related cardiac surgery and valve replacement surgery, HR 117 (95% CI 93.0–148) and HR 74.8 (95% CI 56.4–99.2), respectively. Diabetes mellitus, previous ischemic stroke and presence of an intracardiac electronic device also predicted the risk of IE, however, they were less important predictors (diabetes: HR 1.69, 95% CI 1.01–2.82, ischemic stroke: HR 1.75, 95% CI 1.21–2.52, electronic device: HR 1.59, 95% CI 1.05–2.39). Conclusion: The risk of developing IE was found to be almost 55 times higher in patients with ACHD aged 18–65 years compared with matched controls. Previous ACHD related surgery and valve replacement were the most significant risk predictors. These results underscore the need of continuous clinical follow-up as well as the need of further research to prevent this serious complication of ACHD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The work was supported by grants from the Swedish state under an agreement between the Swedish government and country councils, the ALF-agreement (grant numbers 236611 and 917361); and the Swedish Heart-Lung Foundation (grant number: 20180644 and 20200521).